EFFECTS OF NANO-SIZED BORON NITRIDE ON THERMAL DECOMPOSITION BEHAVIOUR OF EPOXY-BASED INTUMESCENT COATING - ZULKURNAIN, EZA SYAHERA (2016)
Structural steel is integral part of construction industry. In the case of fire, it loses its load bearing capabilities at 500°C and collapse within 45 min. Intumescent fire retardant (IFR) coating is one of the easiest ways of fire protection system. In present research work, IFR coating formulations were developed using ammonium polyphosphate (APP), expandable graphite (EG), melamine (MEL), boric acid (BA) and Bisphenol A with polyamide amine H-2310 as curing agent. Nano-sized boron nitride (BN) and nano-sized alumina (AI2O3) were added as inorganic fillers. The coated steel substrates were subjected to furnace fire test at 500°C for 2h and fire protection test for lh. The coatings were characterized by thermogravimetric analysis (TGA) while the char from fire test were characterized by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The steel substrates were then characterized by optical microscope and Rockwell hardness test.